Citral Delays Postharvest Senescence of Kiwifruit by Enhancing Antioxidant Capacity under Cold Storage - Ling Wei; Chuying Chen; Chunpeng Wan; Ming Chen; Jinyin Chen (Journal of Food Quality)
Citral is an aliphatic aldehyde extracted from citrus essential oil. The aim of the study was to examine how citral treatment affects the weight loss, firmness, respiration, and ripening index, as well as the antioxidant capacity of kiwifruit (Actinidia chinensis cv. ‘Jinkui’). The citral treatment was seen to reduce the weight loss, softening, and fruit respiration compared to control fruits. Citral treatment also had an inhibitory effect on ripening index, O2•− production rate, and malondialdehyde (MDA) accumulation. The degradations of ascorbic acid (AsA) content, total flavonoids content (TFC), and total phenolics content (TPC) were also suppressed by citral. In contrast, citral treatment induces the activation of antioxidant enzyme system such as superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT). Collectively, the results indicated that citral treatment delays postharvest senescence and prolongs storage life by enhancing antioxidant capacity in harvested kiwifruits. These findings suggest that citral has the potential to be used as a promising natural preservative for the extension of postharvest quality in harvested kiwifruit.